PENGARUH E-COMMERCE DAN MEDIA SOSIAL TERHADAP PENJUALAN UMKM DI ERA PANDEMI (STUDI KASUS DESA CIBOLANG) - Umban Adi Jaya; Anugerah Nur Raya (LP2M Universitas Bina Bangsa, 2022)
The purpose of this study is to determine the effect of E-commerce and Social Media on MSME Sales in Cibolang Village in the Pandemic Era. Methodology: The research method used is a survey method using a questionnaire distributed to 62 samples. While the instrument quality testing techniques include validity and reliability tests. The classical assumption test technique uses normality test, multicollinearity test, and heteroscedasticity test. As for testing the hypothesis using multiple linear regression analysis, t test (partial), and f test (simultaneous). Results: (1) the influence of the E-commerce variable on the Sales variable, (2) the absence of the influence of the Social Media variable on the Sales variable (3) the E-commerce and Social Media variables simultaneously affect the Sales variable